Analisis Kepuasan Konsumen Dalam Menggunakan Aplikasi Deal Java (Survei Terhadap Mahasiswa FEBI UINSU Medan) - Dini Safarina; Zuhrinal M Nawawi; Juliana Nasution (Universitas Muhammadiyah Sumatera Utara, 2022)
E-Commerce has a very big impact in the business world, especially in the process of improving the company's marketing in order to achieve the company's own goals, such as having a strong appeal so that many individuals or organizations are interested in running this business. Now more and more online shops have sprung up or companies that sell various kinds of goods by simply creating a website. So the process of ordering goods is communicated via the internet. One of the E-Commerce researched is Deal Java. This study aims to determine the effect of consumer satisfaction factors such as Product Quality (X1), Company Image (X2), and Price (X3) on student satisfaction (Y) as Deal Java consumers. The research method used is quantitative with research results obtained from respondents as many as 98 students through data collection techniques in the form of observation and questionnaires.The data analysis method used is simple regression analysis, namely validity and reliability tests, classical assumption tests, and hypothesis testing. The results showed that product quality had no partial effect on consumer satisfaction. Company image and price partially have a significant positive effect on consumer satisfaction.Then, product quality, company image, and price simultaneously have a significant positive effect on consumer satisfaction.